2006
DOI: 10.1007/s12094-006-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

HER2 (erbB-2)-targeted effects of the ϖ-3 polyunsaturated. Fatty acid α-linolenic acid (ALA; 18:3n-3) in breast cancer cells: the «fat features» of the «Mediterranean diet» as an «anti-HER2 cocktail»

Abstract: i) These findings reveal that the omega-3 PUFA ALA suppresses overexpression of HER2 oncogene at the transcriptional level, which, in turn, interacts synergistically with anti-HER2 trastuzumab- based immunotherapy. ii) Our results molecularly support a recent randomized double-blind placebo-controlled clinical trial suggesting that ALA may be a potential dietary alternative or adjunct to currently used drugs in the management of HER2-positive breast carcinomas. iii) Considering our previous findings demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…, arachidonic acid (AA, C20:4 n -6)-derived eicosanoids) [42,56,78], altering adipokine secretion [54] and interrupting tumorigenic signaling pathways [79]. These chemoprotective effects of n -3 PUFA result in decreased cell proliferation and increased apoptosis, ultimately resulting in reduced BC tumor incidence, growth, multiplicity, and metastasis in rodent models of BC [43,44,46,48,49,50,51,52,53,55,79]. Further, in a model of obese postmenopausal BC, n -3 PUFA supplementation reduced mammary AT inflammation and markers of inflammatory M1 macrophage infiltration [80] which was associated with reduced tumor burden, indicating that the inflammatory microenvironment promotes tumorigenesis and that n -3 PUFA directly antagonize this process.…”
Section: N-3 Polyunsaturated Fatty Acids and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…, arachidonic acid (AA, C20:4 n -6)-derived eicosanoids) [42,56,78], altering adipokine secretion [54] and interrupting tumorigenic signaling pathways [79]. These chemoprotective effects of n -3 PUFA result in decreased cell proliferation and increased apoptosis, ultimately resulting in reduced BC tumor incidence, growth, multiplicity, and metastasis in rodent models of BC [43,44,46,48,49,50,51,52,53,55,79]. Further, in a model of obese postmenopausal BC, n -3 PUFA supplementation reduced mammary AT inflammation and markers of inflammatory M1 macrophage infiltration [80] which was associated with reduced tumor burden, indicating that the inflammatory microenvironment promotes tumorigenesis and that n -3 PUFA directly antagonize this process.…”
Section: N-3 Polyunsaturated Fatty Acids and Breast Cancermentioning
confidence: 99%
“…The inflammatory mammary tumor microenvironment should not be confused with “inflammatory breast cancer” (IBC), a rare (1%–6% of all breast malignancies) aggressive BC subtype with higher grade metastatic hormone receptor negative tumors that has been reviewed elsewhere [25,26]. Moreover, we provide evidence that dietary long-chain (LC) n -3 polyunsaturated fatty acids (PUFA), particularly fish oil (marine)-derived eicosapentaenoic acid (EPA, 20:5 n -3) and docosahexaenoic acid (DHA, 22:6 n 3), which have well established anti-inflammatory effects in obesity [27,28,29,30,31,32,33,34,35,36,37,38,39,40,41] and anti-carcinogenic effects in BC [42,43,44,45,46,47,48,49,50,51,52,53,54,55,56], may represent an effective complementary approach in the prevention and/or treatment of obesity-associated BC by attenuating inflammatory adipokine-mediated paracrine interactions within the mammary tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…the generation of free radicals and lipid peroxidation. 29 Dai et al 30 showed that polyunsaturated fatty acids are cytotoxic to tumor cells, and of the fatty acids tested, linoleic acid (LA) and α-linolenic acid (ALA) were the most effective in suppressing the growth of normal gastric cells ( . The induction of apoptosis by α-linolenic acid (18) (ALA) was observed by Vecchini et al 31 and Scheim 32 and likely occurred because of the reduction of nitric oxide, as proposed by Deshpande et al 33 In recent studies with mouse models, ALA (18) reduced breast tumor growth while increasing the efficacy of chemotherapeutic agents.…”
Section: Resultsmentioning
confidence: 99%
“…excelsa and S. reticulata. 7 The steroids β-sitosterol (30) and stigmasterol (29) are common compounds in species of several genera and families, and the properties of β-sitosterol isolated from S. spectabilis var. excelsa have been reported as antibacterial, antiinflammatory and analgesic.…”
Section: Resultsmentioning
confidence: 99%
“…An increased intake of ALA has been associated with a decrease in blood cholesterol levels, a reduction in the risk of heart attacks, and a growth reduction in breast, colon and prostate cancer [13][14][15][16]. ALA is the precursor of EPA and DHA and it is also stated to have an effect in the production of different eicosanoids, and in lowering the blood pressure as well as blood triglyceride levels [17].…”
Section: Introductionmentioning
confidence: 99%